2010
DOI: 10.1007/s11223-010-9243-z
|View full text |Cite
|
Sign up to set email alerts
|

Approximate analytical method for determining the vibration-diagnostic parameter indicating the presence of a crack in a distributed-parameter elastic system at super- and subharmonic resonances

Abstract: 620.178.5:620.179 and A. P. YakovlevAn approximate method for calculating the vibration-diagnostic parameter indicating the presence of a crack in an elastic distributed-parameter system at super-and subharmonic resonances is considered. The method involves the finding of the non-linearity characteristic of an elastic system based on the analysis of its forced vibrations in the undamaged state and the use of results of the approximate analytical determination of parameters of nonlinearity for vibrations of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Over the last decades, many scholars have exploited the different nonlinear characteristics of beams with breathing cracks by using analytical methods [18][19][20], numerical methods [21,22] and experimental approaches [23,24]. Their studies showed that nonlinear vibration characteristics have a higher sensitivity to breathing cracks, especially the presence of sub-and super-harmonic resonances [25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the last decades, many scholars have exploited the different nonlinear characteristics of beams with breathing cracks by using analytical methods [18][19][20], numerical methods [21,22] and experimental approaches [23,24]. Their studies showed that nonlinear vibration characteristics have a higher sensitivity to breathing cracks, especially the presence of sub-and super-harmonic resonances [25].…”
Section: Introductionmentioning
confidence: 99%
“…Their studies showed that nonlinear vibration characteristics have a higher sensitivity to breathing cracks, especially the presence of sub-and super-harmonic resonances [25]. For example, Matveev et al [18] presented an approximate analytical method to calculate the relative amplitude of the dominant harmonics of a rod-like structure with a closing crack at sub-and super-harmonic resonances, and they showed that the acceleration amplitude of the second harmonic is more sensitive than that of the fundamental harmonic. Bovsunovskii et al [19] developed the dynamic model of a beam with a closing crack which considered the damping change due to crack propagation.…”
Section: Introductionmentioning
confidence: 99%
“…In order to determine the relative amplitude of the dominant harmonics of a rod-like structure with a closing crack at subharmonic and superharmonic resonances, Matveev et al [122] presented an approximate analytical method. They demonstrated that the acceleration amplitude of the second harmonic is more sensitive than that of the fundamental harmonic.…”
Section: Future Researchmentioning
confidence: 99%